Micro Takaful programs for the poor: the Malaysian experience - Rapi, Muh Zul Hazmi; Salaudeen, Adnan Opeyemi; Muhammad Rawi Ravi, Muhammad Imran; Wongsangiam, Rois; Redzuan, Nur Harena (Academic Inspired Network (AIN), 2022)
Microtakaful is a specialised financial product that serves the financial needs of society’s poor and vulnerable segments. The presence of the COVID-19 pandemic has resulted in a massive impact on all sectors of society, especially the B40 group. Therefore, the need for financial products to support the B40 group is essential. The main objective of this paper is to explore the potential roles of the microtakaful in assisting the B40 group in Malaysia in coping with the adverse health effects of the COVID-19 pandemic. The approach used in this paper is qualitative research. The method uses a library-based method that uses existing data (secondary sources) such as journals, books, articles, and other sources related to the microtakaful and COVID-19 pandemic. The study’s findings show that to control the poverty rate due to the impact of COVID-19 on the B40 group in Malaysia in the post covid era, the role of all parties is urgently needed to jointly rebuild the country’s economy after the devastation of the COVID-19 pandemic. Additionally, this study finds several critical roles of microtakaful in assisting the B40 group in Malaysia, such as (i) as a poverty alleviation tool, (ii) as a mechanism to provide Shariah-based protection, and (iii) as a tool to promote financial inclusion. This study positively contributes to stakeholders by ensuring they can provide more microtakaful schemes to benefit low-income earners in the post-COVID-19 pandemic. The study also adds to the literature on the concept of micro-takaful.